Preventive Herd Health Program - Stokka, Gerald L.; Falkner, Thomas R. (My University, 1998)
A guide to using a consistent, annual vaccination program developed by a veterinarian to increase the number of immunized animals.
EP50_1998-11
Keywords: EP50; Livestock; EP